Visualization of natural phenomenon : generation of photo-realistic images of fire, flames and combustion effects - Loke, Teng See. (2009)
In the past decade, there have been some very exciting advancements in the computer graphics community. Many dynamic systems, including natural phenomena, can now be simulated, modelled and rendered realistically on a graphics system. These include mountain, valley, cloud, fog, rain, sea, smoke and fire. This thesis focuses on the modelling and rendering of fire as the author believes that in this area, more refinements and innovative techniques can be developed further. The objective is to create user-controllable colourful, animated and realistic flame images artificially.